Impacts of Trade Liberalization on Poverty and Inequality in Argentina: Policy Insights from a Non-parametric CGE Microsimulation Analysis - Cicowiez, Martín (2010)
This paper studies the economic, poverty, and income inequality impacts of both world and domestic trade reform in Argentina, with a special focus on export taxes. Argentina offers an interesting case study as the only large agricultural exporter that has, at many points in its history, applied export taxes to several of its agricultural products. The paper combines results from a global economy-wide model (World Bank's LINKAGE model), a national CGE model, and microsimulations. The results suggest that full liberalization of world trade (including subsidies and import taxes, but not export taxes), both for agricultural and non-agricultural goods, reduces poverty and inequality in Argentina. However, if only agricultural goods are included, indicators for poverty and inequality do not improve and even deteriorate somewhat. This is particularly the case if export taxes are eliminated.